Mechanism of Endoplasmic Reticulum Stress in Cerebral Ischemia - Han, Yu; Yuan, Mei; Guo, Yi-Sha; Shen, Xin-Ya; Gao, Zhen-Kun; Bi, Xia (Frontiers in Cellular Neuroscience, 2021)
Endoplasmic reticulum (ER) is the main organelle for protein synthesis, trafficking and maintaining intracellular Ca2+ homeostasis. The stress response of ER results from the disruption of ER homeostasis in neurological disorders. Among these disorders, cerebral ischemia is a prevalent reason of death and disability in the world. ER stress stemed from ischemic injury initiates unfolded protein response (UPR) regarded as a protection mechanism. Important, disruption of Ca2+ homeostasis resulted from cytosolic Ca2+ overload and depletion of Ca2+ in the lumen of the ER could be a trigger of ER stress and the misfolded protein synthesis. Brain cells including neurons, glial cells and endothelial cells are involved in the complex pathophysiology of ischemic stroke. This is generally important for protein underfolding, but even more for cytosolic Ca2+ overload. Mild ER stress promotes cells to break away from danger signals and enter the adaptive procedure with the activation of pro-survival mechanism to rescue ischemic injury, while chronic ER stress generally serves as a detrimental role on nerve cells via triggering diverse pro-apoptotic mechanism. What’s more, the determination of some proteins in UPR during cerebral ischemia to cell fate may have two diametrically opposed results which involves in a specialized set of inflammatory and apoptotic signaling pathways. A reasonable understanding and exploration of the underlying molecular mechanism related to ER stress and cerebral ischemia is a prerequisite for a major breakthrough in stroke treatment in the future. This review focuses on recent findings of the ER stress as well as the progress research of mechanism in ischemic stroke prognosis provide a new treatment idea for recovery of cerebral ischemia.